Regional differences in short stature in England between 2006 and 2019: A cross-sectional analysis from the National Child Measurement Programme. - Joanna Orr (Public Library of Science (PLoS), 2021)
Background Short stature, defined as height for age more than 2 standard deviations (SDs) below the population median, is an important indicator of child health. Short stature (often termed stunting) has been widely researched in low- and middle-income countries (LMICs), but less is known about the extent and burden in high-income settings. We aimed to map the prevalence of short stature in children aged 4-5 years in England between 2006 and 2019. Methods and findings We used data from the National Child Measurement Programme (NCMP) for the school years 2006-2007 to 2018-2019. All children attending state-maintained primary schools in England are invited to participate in the NCMP, and heights from a total of 7,062,071 children aged 4-5 years were analysed. We assessed short stature, defined as a height-for-age standard deviation score (SDS) below -2 using the United Kingdom WHO references, by sex, index of multiple deprivation (IMD), ethnicity, and region. Geographic clustering of short stature was analysed using spatial analysis in SaTScan. The prevalence of short stature in England was 1.93% (95% confidence interval (CI) 1.92-1.94). Ethnicity adjusted spatial analyses showed geographic heterogeneity of short stature, with high prevalence clusters more likely in the North and Midlands, leading to 4-fold variation between local authorities (LAs) with highest and lowest prevalence of short stature. Short stature was linearly associated with IMD, with almost 2-fold higher prevalence in the most compared with least deprived decile (2.56% (2.53-2.59) vs. 1.38% (1.35-1.41)). There was ethnic heterogeneity: Short stature prevalence was lowest in Black children (0.64% (0.61-0.67)) and highest in Indian children (2.52% (2.45-2.60)) and children in other ethnic categories (2.57% (2.51-2.64)). Girls were more likely to have short stature than boys (2.09% (2.07-2.10) vs. 1.77% (1.76-1.78), respectively). Short stature prevalence declined over time, from 2.03% (2.01-2.05) in 2006-2010 to 1.82% (1.80-1.84) in 2016-2019. Short stature declined at all levels of area deprivation, with faster declines in more deprived areas, but disparities by IMD quintile were persistent. This study was conducted cross-sectionally at an area level, and, therefore, we cannot make any inferences about the individual causes of short stature. Conclusions In this study, we observed a clear social gradient and striking regional variation in short stature across England, including a North-South divide. These findings provide impetus for further investigation into potential socioeconomic influences on height and the factors underlying regional variation.